2015
DOI: 10.1039/c4cc08414d
|View full text |Cite
|
Sign up to set email alerts
|

Triazolo-β-aza-ε-amino acid and its aromatic analogue as novel scaffolds for β-turn peptidomimetics

Abstract: Triazolo-β-aza-ε-amino acid and its aromatic analogue ((Al)TAA/(Ar)TAA) in the peptide backbone mark a novel class of conformationally constrained molecular scaffolds to induce β-turn conformations. This was demonstrated for (Al)TAA in a Leu-enkephalin analogue and in a designed pentapeptide wherein the FRET process was established. Restricted rotation induced chirality and turn conformation into the achiral aromatic amino acid scaffold, (Ar)TAA, which in a short tripeptide backbone acted as a β-turn mimic as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…To produce a Boc‐protected amino derivative of 3‐ethynylaniline, following a reaction similar to that previously reported, tert ‐butyl(3‐iodophenyl)carbamate (see A in the Supporting Information Figure S3, 700 mg, 2.19 mmol) and [PdCl 2 (PPh 3 ) 2 ] (70 mg, 0.098 mmol) were solubilized in a mixture of benzene (30 mL) and n ‐butyl amine (20 mL) under an argon atmosphere and the solution was degassed by bubbling with argon gas for 10 m. Trimethylsilylacetylene (0.5 mL, 3.3 mmol, 1.5 equiv) and CuI (8.3 mg, 0.04 mmol) were added. The solution was stirred at 80 °C for 24 h. The solvents were evaporated by rotary evaporator and the crude of the reaction was dissolved in ethyl acetate (50 mL).…”
Section: Methodsmentioning
confidence: 99%
“…To produce a Boc‐protected amino derivative of 3‐ethynylaniline, following a reaction similar to that previously reported, tert ‐butyl(3‐iodophenyl)carbamate (see A in the Supporting Information Figure S3, 700 mg, 2.19 mmol) and [PdCl 2 (PPh 3 ) 2 ] (70 mg, 0.098 mmol) were solubilized in a mixture of benzene (30 mL) and n ‐butyl amine (20 mL) under an argon atmosphere and the solution was degassed by bubbling with argon gas for 10 m. Trimethylsilylacetylene (0.5 mL, 3.3 mmol, 1.5 equiv) and CuI (8.3 mg, 0.04 mmol) were added. The solution was stirred at 80 °C for 24 h. The solvents were evaporated by rotary evaporator and the crude of the reaction was dissolved in ethyl acetate (50 mL).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the tendency of β-turn formation for this Tz amino acid system in tri and pentapeptides has been described. [17,18] It has been also shown that a 1,4-Tz amino acid can replace a dipeptide in an α-helical secondary structure. [19,20] Oligomers of triazole, also called triazolamers have been rarely described.…”
Section: Introductionmentioning
confidence: 99%
“…There have been two strategies of molecular design to mimic β-strand structures and hydrogen-bonding β-sheet structures. One is the use of nonpeptidic scaffolds to attain shape similarities to β-strand-like extended structures, and the other is utilizing amino acids and amino acid surrogates to stabilize interstrand hydrogen-bonding β-sheet structures, which includes macrocyclization (backbone or side chain to side chain) and replacement of amino acids. A major difference between these two strategies is the absence or presence of the ability to form interstrand hydrogen bonding. Many examples of the former approach have been reported using various nonamino acid units such as dibenzofurans, , oligoureas, metallopeptides, indolin-3-ones, imidazolidin-2-ones, epiindolines, and oligothienylpyridines .…”
Section: Introductionmentioning
confidence: 99%